2001
DOI: 10.1080/09712119.2001.9706759
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dry Yeast (Saccharomyces cerevisiae) Compounds in the Feed to Reduce Aflatoxin B1(AFB1) Residues and Toxicity to Japanese Quails (Coturnix coturnix japonica)

Abstract: Celik, I<., Denli, M., Erturk, M., Ozturkcan, 0. and Doran, F. 2001. Evaluation of dry yeast (Saccltaromyces cerevisiae) compounds in the feed to reduce aflatoxin B, (AFB,) residues and toxicity to Japanese quails (Coturnis coturnix japonica). J. Apa. h i m . Res., 20: 245-250.To study the effects of dry yeast (Saccharomyces cerevkiae) as adsorbent when given a h t o x i n B, (AFBJ on the weight gain, feed consumption, feed conversion ratio, pathological alterations and serum parameters, 200 Japanese quail chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
(8 reference statements)
4
9
0
3
Order By: Relevance
“…The difference may be fully explained by the occurrence of better gut microorganisms and pathogen reduction t h a n o t h e r s . P a n d a et al (2000) indicated t h a t feeding of antimicrobials and sub-therapeutic levels of antibiotics results in suppression of bacteria responsible for mild but unrecognizable infections, reduced production of growth depressing toxins from Celik et al, 2001) agree with this report showing good growth performance i n SC group. This study demonstrates that the flavomycin supplemented group of birds had the maximum weight gain followed by Saccharoinyces cerevisiae, control and bioteksin-L supplemented birds, respectively, at the end of 6 weeks of feeding.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The difference may be fully explained by the occurrence of better gut microorganisms and pathogen reduction t h a n o t h e r s . P a n d a et al (2000) indicated t h a t feeding of antimicrobials and sub-therapeutic levels of antibiotics results in suppression of bacteria responsible for mild but unrecognizable infections, reduced production of growth depressing toxins from Celik et al, 2001) agree with this report showing good growth performance i n SC group. This study demonstrates that the flavomycin supplemented group of birds had the maximum weight gain followed by Saccharoinyces cerevisiae, control and bioteksin-L supplemented birds, respectively, at the end of 6 weeks of feeding.…”
Section: Resultssupporting
confidence: 82%
“…These have been derived from the yeast cell wall, which exhibits a high degree of antigenicity mainly due to mannan and glucan components. Mannose sugars in the mannanoligosaccharides influence the immune system by stimulating the secretion of mannose-binding protein from liver which binds to the capsule of invading bacteria and triggers the complement fixation system (Celik et al, 2001). In agreement with previous studies (Maizzo et al, ZOOl), SC could be a natural growth promotor for broilers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they were diminished products of aflatoxin in both the in vitro and in vivo studies [105]. The beneficial effects of Saccharomyces cerevisiae in management of aflatoxin B1 toxicity has also been evaluated in broilers [106] and Quails [107]. Bueno et al [108] has also demonstrated that Saccharomyces cerevisiae is an important and efficient micro-organism in aflatoxin B1 quenching.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…A variety of adsorbents such as bentonite [9], zeolite [10], hydrated sodium calcium aluminosilicate [11], Saccharomyces cerevisiae [12], and activated charcoal [13], have been successfully used in detoxifying afl atoxins in contaminated feeds [14,15]. Adsorbent compounds utilized to ameliorate and Lymphoid Organs in Broiler Chicken.…”
Section: Introductionmentioning
confidence: 99%